Extracting the mean size across the visual field in patients with mild, chronic unilateral neglect - Yamanashi Leib, Allison; Landau, Ayelet N.; Baek, Yihwa; Chong, Sang Chul; Robertson, Lynn (Frontiers in Human Neuroscience, 2012)
Previous studies suggest that normal vision extracts statistical information from sets of objects across the visual field (e.g., mean size). In this study, we explore whether patients with left unilateral neglect extract statistical summaries in a typical manner. We tested 4 patients with left unilateral neglect using a visual search task that varied the mean size of a group of circles within the display. The task was to report whether a target circle was present or not. On each trial, we first presented a single circle in the center of the screen (the target) which varied in size from trial to trial. The circles in the subsequent search display varied in size but were grouped together either on the left or right side of the display. The circles were accompanied by a group of irrelevant triangles that did not vary in size and appeared on the opposite side of the display. On 50% of trials the mean size of the circles was the size of the target and on 50% the mean size was different from the target. We analyzed accuracy when the circles were on the left compared to the right side of the display. When the targets were absent, patients produced more false alarms on the contralesional side when the mean size of the group was the target size than when it was not, a typical pattern of response demonstrating that the distractors on the ipsilesional side could be rejected in the summary statistic of the group of circles. Conversely, the ipsilesional side did not produce this difference, and if anything showed the reverse pattern. Further analyses demonstrated that the size of the distractor triangles on the contralesional side were pooled with ipsilesional circles under these conditions (i.e., distractor size could not be rejected and thus distorted the group summary statistic). These findings are discussed as they relate to statistical summary processing in patients with spatial attention deficits and to their performance on visual search tasks.